THE SEROK RIVER CATCHMENT FLOOD HYDROGRAPH - Herlianda, Herlianda; Nurhayati, Nurhayati; Yulianto, Eko (Fakultas Teknik Universitas Tanjungpura, 2023)
Global climate change is expected to cause an increase in the intensity and duration of extreme rainfall events that occur today. The leading cause of flooding in various world regions, including flat coastal areas such as the Serok River catchment in Kota Pontianak, influenced by tides, is excessive rainfall. This article presents the results of an analysis of the impact of extreme precipitation on the peak discharge of flood hydrographs in the Serok River catchment, Kota Pontianak.Maximum daily rainfall data for 2009-2020 recorded at PTK-11 Pontianak Station were selected using the Annual Maximum Series Method. Frequency analysis was conducted using the best distribution method selected from Normal, Log Normal, Log Pearson Type III, and Gumbel Type I to obtain the design rainfall. The design rainfall was transformed into flood hydrographs at the next stage using the Snyder Synthetic Unit Hydrograph based on several return periods.The results of the analysis show that there are changes in flood discharge in the Serok River catchment area for each return period. The location of land use and the value of rain intensity significantly affect the calculation of plan discharge; the more significant the land area and the higher the rain intensity, the greater the resulting release. The most considerable flood discharge (Qmax) in the 2, 5, and 10 years return occurs at STA 1 + 100, w.290 m3/s, 0.347 m3/s, and 0.377 m3/s, respectively. Thus, this causes periodic flooding/inundation conditions, especially in areas that have low elevations.